Recent Progress on Electrocatalyst and Photocatalyst Design for Nitrogen Reduction. Issue 6 (19th November 2018) - Li, Mengqiao; Huang, Hao; Low, Jingxiang; Gao, Chao; Long, Ran; Xiong, Yujie
Abstract: Ammonia is one of the most important chemicals due to its enormous applications in fertilizer production and as an energy carrier. The production of ammonia mainly relies on the traditional Haber–Bosch process under high temperature and pressure, leading to massive energy consumption and notable environmental issues. Recently, electrocatalytic and photocatalytic nitrogen (N2 ) fixation have emerged for achieving green production of ammonia owing to their features of environmental friendliness and cost‐effectiveness. However, ammonia production through electrocatalysis and photocatalysis is still far away from practical applications. To facilitate the practical applications, a thorough understanding of nitrogen fixation is highly desired for the future design of high‐efficiency catalysts. Here, the fundamental investigations on electrocatalytic and photocatalytic N2 reduction are summarized. Based on the fundamental understanding, the current approaches and design strategies for heterogeneous catalysts toward electrocatalytic and photocatalytic N2 reduction are then presented. Finally, the remaining challenges and future opportunities in this field are outlined, leveraging the existing understanding on structure–property relationships. It is anticipated that this review sheds some light on the development of advanced catalytic systems for ammonia production through N2 fixation. Abstract : Nitrogen reduction under mild conditions has been developed rapidly in recent years. Here, the fundamental mechanisms behind the reported cases together with the designing rules for electrocatalytic and photocatalytic nitrogen fixation toward efficient nitrogen reduction are discussed.